ANALISIS KELAYAKAN FINANSIAL KELAPA SAWIT DI KABUPATEN LAMPUNG TENGAH - Syafri Alfizar; Ali Ibrahim Hasyim; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The purpose of this research is to determine the financial feasibility of palm oil.  The research was conducted in Bangun Rejo Subdistrict and Bekri Subdistrict Central Lampung District in April - May 2016.  The sampling technique of this research is purposive sampling.  The method used in this research is a survey method.  The population of palm oil farmers who have plant age 5 - 10 years in  Binjaingagung village are 54 people and the population of palm oil farmers in Sidoluhur village are 118 people. The number of respondents in this research were as many as 27 farmers from both villages.  Data were analyzed using financial analysis of quantitative and qualitative.  The results of this research showed that financially farming palm oil in Central Lampung is feasible and profitable based on the Net B/C of 24.84, Gross B/C of 5.61, PP 6.24, NPV 167,455,232.56, and  IRR 47 percent. Palm oil farming is not sensitive to cost increase of 7.26 percent, but is sensitive to price reduction of 25 percent and decline in production of 18 percent.Key words : financial feasibility, palm oil, sensitivity